Angiopoietin switching regulates angiogenesis and progression of human hepatocellular carcinoma. Issue 11 (4th November 2003) - Sugimachi, K; Tanaka, S; Taguchi, K; Aishima, S; Shimada, M; Tsuneyoshi, M
Abstract : Aim: Angiopoietin 1 (Ang-1) and its antagonist, angiopoietin 2 (Ang-2), are novel ligands that regulate the Tie2 receptor. The Ang-2 gene is upregulated in the hypervascular type of human hepatocellular carcinoma (HCC). To gain a better understanding of the role of the Ang–Tie2 system in HCC the expression of these genes was investigated in a series of human HCCs. Methods: The expression of the angiopoietin and Tie2 proteins was investigated in nine normal liver tissues and 52 surgically resected HCCs. In addition, the effects of hypoxic stimuli on Ang-1, Ang-2, vascular endothelial growth factor (VEGF), and erythropoietin (EPO) expression was investigated in Hep3B cells. Results: Ang-1, rather than Ang-2, was more frequently expressed in the normal liver. Ang-1 was expressed in 68% of HCCs, whereas Ang-2 was expressed in 81%, and was significantly higher in poorly differentiated HCCs characterised by high vascularity (p = 0.02), and in tumours with a peliotic change (p = 0.02). Strong expression of Tie2 was seen in tumour vessels in accordance with Ang-2 expression. In Hep3B cells, hypoxic stimuli upregulated VEGF and EPO, but not Ang-1 or Ang-2. Conclusions: These data support the evidence that the reversal of Ang-1 and Ang-2 expression plays an important role in the angiogenic and dedifferentiation processes in HCC. The hypoxic stimuli were not responsible for Ang-2 upregulation, unlike that of VEGF, in human HCC cells.